2010
DOI: 10.1158/1078-0432.ccr-09-3200
|View full text |Cite
|
Sign up to set email alerts
|

CK2 Modulation of NF-κB, TP53, and the Malignant Phenotype in Head and Neck Cancer by Anti-CK2 OligonucleotidesIn vitroorIn vivovia Sub–50-nm Nanocapsules

Abstract: Purpose: The aim of this study is to investigate the expression of CK2 subunits and CK2 effects on NF-κB-mediated and TP53-mediated signal activation and gene expression, the malignant phenotype, and chemosensitivity in head and neck squamous cell carcinoma (HNSCC) in vitro and in vivo.Experimental Design: Protein expression of CK2 subunits was investigated by Western blot and immunohistochemistry. CK2 subunits were knocked down by small interfering RNA, and NF-κB activation was examined using DNA binding, Wes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(137 citation statements)
references
References 45 publications
8
128
0
1
Order By: Relevance
“…These findings promote CK2 as an unfavorable prognostic marker in several cancers and consequently as a relevant therapeutic target (Prudent et al, 2010;Sun et al, 2010;Trembley et al, 2010). Recent studies report that CK2 contributes to aberrant NF-B activation though enhancement of IKK␤ activity for the phosphorylation of the Ser32/Ser36 NH 2 terminus of IB␣, a novel and distinct function from that of CK2 as a known COOH-terminal IKK␤ (Yu et al, 2006;Brown et al, 2010). Inverse docking indicated that CK2 may be a potent target of LYG-202 in blocking of NF-B activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings promote CK2 as an unfavorable prognostic marker in several cancers and consequently as a relevant therapeutic target (Prudent et al, 2010;Sun et al, 2010;Trembley et al, 2010). Recent studies report that CK2 contributes to aberrant NF-B activation though enhancement of IKK␤ activity for the phosphorylation of the Ser32/Ser36 NH 2 terminus of IB␣, a novel and distinct function from that of CK2 as a known COOH-terminal IKK␤ (Yu et al, 2006;Brown et al, 2010). Inverse docking indicated that CK2 may be a potent target of LYG-202 in blocking of NF-B activation.…”
Section: Discussionmentioning
confidence: 99%
“…We know that TNF-␣ triggers both the caspase-protease pathway and the NF-B pathway, and the balance of these two pathways is critical for the ultimate fate of a cell: death or survival (Brown et al, 2010). These findings prompted us to determine whether LYG-202 could enhance TNF-␣-induced apoptosis by attenuating the NF-B pathway.…”
Section: Lyg-202mentioning
confidence: 99%
“…Indeed, sensitization of pancreatic cancer cells to gemcitabine and head and neck cancer cells to cisplatin by genetic manipulation of CK2 expression has been attributed to resulting suppression of Akt and NF-kB activity, respectively (47,48). Thus it is possible that in addition to the suppression of DNA repair response, CX-4945 enhances activity of gemcitabine and cisplatin by modulating PI3K/Akt and NF-kB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…siRNA against CK2 subunits was encapsulated inside tenfibgen nanocapsules and administered by intratumoural injection into a HNSCC xenograft animal model, resulting in suppression of tumour size accompanied with modulation of CK2 and NF-kappaB regulated molecules and induction of apoptosis (Brown et al, 2010). Another Phase I clinical trial (Atu027) has been announced by Silence Therapeutics to treat a broad range of solid tumours including gastrointestinal (including pancreatic), non-small cell lung, prostate, melanoma, liver and others (www.silence-therapeutics.com).…”
Section: Delivery Of Sirna In Cancer Therapymentioning
confidence: 99%